Catalyzing the urban surface: strategizing sites along the historic Smoky Hill River corridor - Debold, Ryan J. (Kansas State University, 2010)
The trend of urbanization is escalating on a global scale, in many cases sprawling outward at the expense of decaying urban centers, post industrial infrastructure, and other neglected landscapes. There is a critical need for intelligent, responsive, and resilient urban planning and design. The Smoky Hill River’s neglected cutoff channel running through the heart of Salina, Kansas, is exemplary of these phenomena. Although the historic channel operates as an important landscape infrastructural system for stormwater conveyance, it remains largely inactive in terms of its connections to adjacent neighborhoods, cultural significance, and economic driving potential. Landscape Urbanism, a relatively new realignment in urbanism theory, involves the concept of engaging dynamic urban processes and facilitating or enhancing relationships through design, providing potential remediation to many urban dilemmas. While still speculative and experimental, its application in metropolitan environments has garnered acknowledgment in the design community. Landscape Urbanism’s relevance toward micropolitan and small metropolitan cities, however, remains largely unexplored. The relationship between the revitalization of the historic Smoky Hill cutoff and Salina, facilitated by local advocates the Friends of the River, explores the application of Landscape Urbanism theory in smaller urban environs. Through the analysis of precedents exhibiting Landscape Urbanism strategies, the careful inventory of characteristics unique to specific sites along the historic channel, and synthesizing the Friends of the River goals and objectives, applicable strategies that influence design methodology by engaging key urban systems are found and applied. The design of these sites act to “catalyze” adjacent areas through connectivity and enhancing the cultural, environmental, and economic health of the district. Design implementation at a strategic site catalyzes immediately adjacent districts, followed by the catalysis of the entire channel. In its final state, the historic channel becomes re-integrated into the City of Salina as a vital system, engaging and enhancing the urban field as a whole.
Keywords: Landscape urbanism; Smoky Hill River; Salina, Kansas; sprawl; urban catalyst; urban framework; Landscape Architecture (0390); Urban and Regional Planning (0999)